PERANCANGAN APLIKASI KASIR PENJUALAN MORING (CIMOL KERING) BERBASIS ANDROID DENGAN MENGGUNAKAN METODE PROTOTYPE DI UMKM KOTA BANJAR (STUDI KASUS : R3 SNACK) - Romyali, Rommy; Sidiq, Maulana; Mulyana, Dadan (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
Research in this program was carried out to help business UMKM owners in solving problems, entering and exiting products for sale, recording inventory of products ready to be sold and the amount of profit obtained from sales. So far, owner registration is still very simple, some people even don't record it at all. The aim of taking this topic is to help make it easier for owners as business UMKM actors to control the sales of their products and to help them more easily know the size of the profits obtained from their sales. Using this sales cashier application can make it easier to check the amount of inventory, find out the number of products sold, and the profits obtained from sales.